Factors that Influence Stunting in the Maratua District of Berau, Indonesia - Tambunan, Risa Haryati; Nurbaeti, Elis (Folia Medica Indonesiana, 2024)
Highlights: 1. This study investigated the factors contributing to stunting in a remote area, which has not received sufficient attention from key stakeholders. 2. The findings of this study can serve as a reference for the government in addressing stunting through intervention strategies that incorporate paternal roles to improve children's nutritional status. Abstract Stunting is a community health problem with significant impacts. The estimated prevalence rate of stunting was 24.4% in Indonesia and 25.7% in the Berau Regency. Stunting is a growth disorder caused by chronic malnutrition during the first 1,000 days of life. It is characterized by a height-for-age Z-score below -2 standard deviations from the child growth standards median of the World Health Organization, an insufficient growth rate, and a reduced potential final height. The contributing factors to stunting include maternal variables, as mothers are the primary caregivers. The objective of this study was to determine the factors for stunting and specifically investigate if there is a relationship between maternal employment and stunting in the Maratua District of Berau, Indonesia. This study used a cross-sectional research design. The sample size was determined using the Sample Size Calculator from the World Health Organization for a two-sided test (α = 0.05; β = 0.2; p1 = 0.63; p2 = 0.25; 95% CI). The data were collected from the nutrition report and anthropometric measurements at Maratua Primary Healthcare Center. The research was carried out at the Integrated Health Posts (Pos Layanan Terpadu/ Posyandu) in the Maratua District. The toddlers (n = 56) were examined with their parental consent. Toddlers with overnutrition, obesity, and acute infectious diseases were excluded from this study. The data were processed using Chi-square and Fisher tests (p < 0.05). In the analysis, no significant relationship was found between stunting and maternal employment. However, the results revealed that fathers who were not fishermen had a 6.3 times greater risk of having stunted toddlers compared to fathers who worked as fishermen. Fathers with a junior high school degree showed a 6.1 times higher risk of having stunted toddlers than fathers with different educational levels. In conclusion, stunting in the Maratua District is associated with the fathers' educational attainment and employment.